Vocal and Prosodic Parameters on Transgender Digital Influencers’ Speech on Brazilian Social Media - Soncin, Geovana [UNESP]; Bafum, Eryne Alves [UNESP]; Gonçalves, Gabriela Aparecida Rodrigues [UNESP]; Borges, Giovanna Caroline [UNESP]; Santos, Karoline Araujo Dos [UNESP]; Fabbron, Eliana Maria Gradim [UNESP] (Faculdade de Letras da UFMG, 2024)
Voice and prosody in speech of transgender Brazilian digital influencers were analyzed, using perceptual assessment and acoustic analyses to identify similarities and differences. Acoustic speech patterns between transgender (trans) and cisgender (cis) men and women were also compared. Speech samples analyzed consisted of audios from twelve selected videos published on Instagram. In a blinded perceptual assess-ment, judges evaluated how they judged the speaker’s gender and identified prosodic boundaries and promi-nences used for expressive purposes. In the acoustical analysis, the voice was measured by the fundamental frequency; prosodic boundaries were measured by f0 variation of pause production; also, prominence mark-ing was measured by f0 variation and intensity. Results show that transgender subjects’ speech, either by their vocal expression or by their prosodic characteristics, is not perceived exclusively through the recovery of acoustical patterns. Acoustic parameters measured in speech of transgender subjects in comparison with speech of cisgender subjects showed that transgender speech is dialectically constituted, since there are points of approximation and distancing between the characterization of vocal and prosodic aspects of their speech and the characterization of these aspects in speech of the declared gender.
Parâmetros vocais e prosódicos na fala de influenciadores digitais transgênero da mídia social brasileira
Keywords: acoustical analysis; auditory assessment; identity representations; prosody; transgender